Design of Web-based Monitoring System to Measure Overall Equipment Effectiveness (OEE) on Steel Wire Drawing Machine - Hanif, Ibadurrahman; Bukhori, Iksan; Rachmat, Rudi Surahdi (President University, 2024)
Â Abstract-Optimizing production effectiveness is vital for competitiveness in modern manufacturing. One approach to minimizing waste is known as the Six Big Losses. A key tool for identifying these losses and assessing production efficiency is Overall Equipment Effectiveness (OEE), which requires complete and reliable data for accurate calculation. This study presents a web-based OEE monitoring prototype using automated data recording and processing, tested on a steel wire drawing machine at XYZ LLC. The system incorporates an inductive proximity sensor, pulse meter, counter meter, and a PC, with Node-RED handling data collection and transmission to a server for real-time visualization. Testing showed 100% accuracy in speed measurement and product counting, with an average latency of 415.55ms. OEE values slightly decreased from 55% (manual recording) to 53.5% (automated). The prototype effectively delivers accurate, real-time OEE data with an interactive interface, showcasing its potential for manufacturing applications.